Valoração econômica dos danos ambientais de Mariana: uma análise a partir do método de valor contingente - Rafael Silva e Sousa (2021)
The rupture of the ore tailings dam in Mariana - MG, in 2015 is considered the largest environmental disaster in Brazil's history. In an event of such magnitude it is necessary to indentify the economic value of the ambiental losses. Given this context, the objective of this dissertation was to analyze the application of the Contingent Valuation Method (CVM) for the valuation of environmental losses resulting from the disaster. For this purpose, the components of the valuation were evaluated from sociodemographic information contained in the questionnaires applied to a treatment and a control group. Multiple linear regressions were estimated in order to capture the relationship between the characteristics and the willingness to pay (WTP) by an improvement in the condition of the valued resources. A possible difference between the WTP's controlled by the socio-demographic characteristics of the two groups was also investigated. To this end, Oaxaca-Blinder decomposition was used. The results found indicate a consistent application of CVM in this case, while most of the explanatory variables used showed a signal consistent with that found in other empirical studies. The predicted WTP's between the treatment group and the control group for the valued resources differ from each other. A big part of the difference was represented by unexplainable factors, i.e., the two groups had homogeneous socio-demographic characteristics, but one year more than one characteristic had a much greater effect on WTP's for one group than for another. It is argued that the differences found reflect the value of the loss of those affected by disaster, since this would modify the marginal sensitivity of attributes on the WTP. The differences may also reflect the existence of the strategic bias in the application, since the respondents knew that the application was intended to mark compensation to the affected by the disaster.